Coordinated control of steer‐by‐wire and brake‐by‐wire for autonomous emergency braking on split‐μ roads. Issue 14 (5th March 2021) - Xue, Zhongjin; Li, Chenfeng; Wang, Xiangyu; Li, Liang; Zhong, Zhihua
Abstract : Autonomous emergency braking (AEB) is an active safety technology which aims to prevent collisions by operating harsh braking. When AEB is activated on split‐μ roads, the yaw moment generated by the asymmetric braking forces will lead to losing control of the vehicle. In this study, a coordinated control scheme of steer‐by‐wire (SBW) and brake‐by‐wire (BBW) is developed to solve this problem. An anti‐lock braking system is achieved by a sliding mode controller. Besides, two model predictive controllers based on a 7‐degree‐of‐freedom vehicle dynamics model are proposed for different road adhesion conditions. According to the simulation results, the proposed scheme can maintain the stability of the vehicle and achieve a satisfying braking efficiency under various friction differences between the two‐side wheels. At last, the experiments are also carried out to verify the effectiveness and the real‐time performance of the proposed scheme on a hardware‐in‐loop bench of BBW and SBW.